THE EFFECT OF THE OTAGO EXERCISE PROGRAM AND BRIDGING EXERCISE IN THE ELDERLY WITH THE RISK OF FALL IN RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO: A CASE REPORT - Wahyundari, Dhanti; Naufal, Adnan Faris; Wijayaningsih, Anteng (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Falls` is the third leading cause of disability among the elderly and a public health problem with major social impacts worldwide in countries with significantly aging populations. More than 30% of people over the age of 65 fall each year and half of the cases fall again. Dynamic balance and leg muscle strength have a close relationship with the risk of falling. Reduced hip muscle activity also affects the body's ability to maintain balance which has negative consequences on functional performance. Case Presentation: Mr. IW is 74 years old with complaints of pain from the lower back sometimes radiating to the left side of the leg since 1 year ago. The left lower leg feels heavy and the pain increases when doing strenuous activities and walking long distances. Complaints reduced with rest. The patient's history of comorbidities has heart disease and gout. Management and Outcome: Patients received the Otago Exercise Program and Bridging Exercise in 1 month with a prescribed dose. Based on the results of the BBS examination, 30 second Chair Stand, TUG Test, and the Indonesian version of the ODI modification, there was an increase in balance and muscle strength of the lower extremities as well as an increase in functional activity seen in patients Discussion: History of low back pain that can causes changes in balance and postural control so that it has a higher postural sway and greater displacement of the center of pressure. For the elderly to be able to enjoy a healthy life and be free from worries about accidents that result in bruises such as falls, they need good muscle strength and balance skills. Lower leg muscle weakness is one of a predictor of falls. Another study found that regular exercise, lumbar muscle strengthening exercises and balance exercises were effective in preventing injury in the elderly and improving the function of the sensory-motor system, which is necessary to keep the body safe. The specially designed OEP consists of strengthening and balance exercises targeting and improving dynamic balance outcomes in the elderly. Core strengthening exercise in the form of Bridging Exercise can restore the body's postural control function and increase range of motion and is considered an appropriate exercise for the elderly. Conclusion: Physiotherapy programs for the elderly at risk of falling using the Otago Exercise Program and Bridging Exercise can improve balance and muscle strength in the lower extremities as well as increase the ability to functional activity in elderly individuals.